Hubungan Dukungan Keluarga dan Kepatuhan Diet Pasien Diabetes Melitus di Indonesia: Tinjauan Pustaka 2022-2025: - - Asmara, Satria Akbar Putra (Yayasan Jompa Research and Development, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by progressive dysfunction of pancreatic beta cells. In 2019, the International Diabetes Federation (IDF) stated that Indonesia ranked seventh out of ten countries with the highest number of diabetes sufferers, namely around 10.7 million people. A literature review was conducted by searching for articles in the Google Scholar, PubMed, and Sciencedirect databases. A total of 24 journals were included in the review. The literature review revealed that family support is associated with dietary compliance in patients with diabetes mellitus. It is hoped that families will provide support to patients with diabetes mellitus to improve their dietary compliance.